Silk garments plus standard care compared with standard care for treating eczema in children: a randomised controlled, observer blind, pragmatic trial (CLOTHES Trial) - Thomas, Kim S.; Bradshaw, Lucy E.; Sach, Tracey H.; Batchelor, Jonathan M.; Lawton, Sandra; Harrison, Eleanor F.; Haines, Rachel H.; Ahmed, Amina; Williams, Hywel C.; Dean, Taraneh; Burrows, Nigel P.; Pollock, Ian; et al. (Public Library of Science, 2017)
Background